Dilution effects, population growth and economic growth under human capital accumulation and endogenous technological change - Alberto Bucci; Levent Eraydın; Moritz Müller (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2018)
This paper answers the following two questions: 1) In the data, can we find a dilution effect of population growth also on per-capita human capital investment? If yes, 2) how can we use this fact to explain theoretically the existence of a differential impact of population change on economic growth across countries? In the first part of the article we document empirically the considerable across-countries heterogeneity of a dilution effect of population growth also in regard to the process of per-capita human capital formation and observe that, at a country's level, population growth may be relevant (either positively or negatively) for economic growth depending on the specific way it affects the process of schooling-acquisition by agents. In the second part of the paper we use these results in order to build a multi-sector growth model which is capable of accounting (depending on the strength of the found dilution effect of population growth on per-capita human capital formation) for the non-monotonous correlation between demographic and economic growth rates in the long-run.
urn:nbn:de:swb:90-798849
Keywords: J10; J24; O33; O41; 330; Human Capital Investment; Economic Growth; Population Growth; Dilution Effects; Research & Development